ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KARET DI INDONESIA - Nurul Alinda (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2013)
Rubber plant (bevea brasiliensis) constitute one of pledge export trade goods. Indonesia even have once become nature rubber producer number one at the world. Largely this plant is contrived by people. Indonesian position as producer of nature rubber universalizes to be now was angled by Malaysia and Thailand, effect acreage extent that we has be not been escorted with big production and good quality. Rubber constitutes commodity the most be relied at agribusiness sector. Volume and Indonesian rubber export point up to year 2005.1 2010.4 point out developings that fluktuatif, where is happening step-up on year 2005 2007. Meanwhile enters year 2008 2009 its growth negatives get bearings by mark sense crisises at United States Of America, where does that state constitute one of rubber importer state is outgrown from Indonesia. Besides another causal factor to be predicted is begat from international price condition, changing exchange rate, and inflation distortion. But on year 2010 ascension happening or fixed up good rubber export conditions of volume facet and also its export points.